(untitled) (Bangladesh Journal of Medical Science, 2018)
Objective: To assess the metabolic syndrome (MetS) status in pre and post menopausal women of Bangladesh. Materials and Methods: Secondary analysis from a cross-sectional study on 276 willing females from an urban and a rural area. The socio-epidemiologic factors were studied with anthropometric examination, blood pressure recording and fasting blood for analysis of triglyceride (TG), high density lipoprotein (HDL), fasting blood sugar (FBS) between pre and post menopausal women. Results and Discussion: Only 19.8% premenopausal women had MetS (95% CI=15.7%-24.7%) compared to that of 50% (95% CI=39.9%-60.1%) menopausal (p<0.001). Low HDL cholesterol prevailed in almost 97% respondents in both groups (p=0.12). The menopausal women had higher TG (51.6%, p=0.07), obesity (10.9%, 0=0.004), high FBS (40.6%, p<0.001) and hypertension (HTN, 32.8%, p<0.001) compared to those of (TG 39.3%, obesity 6.1%, high FBS 19.8% and HTN 9.9% respectively) premenopausal women. On logistic regression, HTN (OR=3.8, 95%CI: 1.9-7.7) and high FBS (OR=2.2, 95%CI: 1.1-4.2) produced significantly higher odds of being associated with menopause. Only menopause became significantly associated with MetS (OR=4.3, 95%CI: 23.0-7.9) after adjusted with residence and education of the respondents. Conclusion: MetS is highly prevalent in post menopausal women in Bangladesh. Women approaching menopause should be brought under health education scheme for awareness of MetS while aging. Bangladesh Journal of Medical Science Vol.17(1) 2018 p.42-46